Making the Switch: Experiences and Results from Converting a Biostatistics Course to Flipped and Online Formats for Public Health Students. Issue 1 (2nd January 2023) - George, Brandon J.; Leon, Juan
Abstract: The recent rise in online learning in statistics has made it essential for instructors to teach effectively in that modality. In this retrospective, we reflect on how online course content was added to an introductory statistics course in a graduate public health program and how it was updated over time based on student feedback and instructor experiences. The impetus for the inclusion of online learning as well as the consequences of specific implementations are discussed for hybrid and fully online class formats. We found that while online learning seemed to be beneficial as a whole for public health students learning health statistics, identifiable differences in the design or implementation of lectures, software demonstrations, online discussion, computer lab activities, active learning, and homework assignments had a substantial effect on learning outcomes and student satisfaction.